Predictors of a Positive Duplex Scan in Patients with a Clinical Presentation Compatible with Deep Vein Thrombosis or Cellulitis - Curtis E Rabuka; Laurent Y Azoulay; Susan R Kahn (Canadian Journal of Infectious Diseases)
BACKGROUND: Deep vein thrombosis (DVT) and cellulitis are common conditions whose symptoms lead patients to seek medical attention in the emergency department (ED). Distinguishing between these two conditions quickly and accurately is important.